1993
DOI: 10.1557/proc-297-939
|View full text |Cite
|
Sign up to set email alerts
|

2D Image Sensing Arrays with NIP Diodes

Abstract: 2D image sensor arrays made with a-Si devices on glass over large area are of considerable interest as document scanners and in medical applications. We have made a test array containing a-Si NIP diodes for both the sensors and the active matrix switching devices. The issues of vertical crosstalk and image lag are discussed in relation to the device performance of the switching diode. The vertical crosstalk is controlled by the diode capacitance and the image lag by the high transient current in the device. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In the majority of these imaging devices, the pixel switch is a single thin-film transistor ͑TFT͒ made from amorphous silicon ͑a-Si:H͒ 1-6 although alternative approaches employing a cadmium selenide TFT, 7 a single a-Si:H diode, [8][9][10] or dual a-Si:H diodes 11 have also been reported. AMFPIs may further be divided into two categories depending upon whether the incident radiation is detected directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of these imaging devices, the pixel switch is a single thin-film transistor ͑TFT͒ made from amorphous silicon ͑a-Si:H͒ 1-6 although alternative approaches employing a cadmium selenide TFT, 7 a single a-Si:H diode, [8][9][10] or dual a-Si:H diodes 11 have also been reported. AMFPIs may further be divided into two categories depending upon whether the incident radiation is detected directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…At biases higher than 0.75 V, where the current-voltage dependence is nonexponential, the forward current is space charge limited. 9 The reverse bias leakage current is one of the most important characteristics of the photodiode array since it determines the lowest detectable light level. For the fabricated photodiodes, the reverse dark current density is around 0.5 nA/cm 2 at Ϫ5 V bias, which is a little higher than the junction leakage reported for a-Si:H p-i-n photodiode arrays with continuous intrinsic layers.…”
Section: Photodiode Array Design and Fabricationmentioning
confidence: 99%
“…There are few reports on the successful implementation of the switching diodes for signal readout in flat-panel x-ray detectors and image sensors. [7][8][9] Switching diodes and photodiodes can be manufactured simultaneously using the same n-i-p layers, and the number of masks required in lithography can be reduced to 6 -7. The disadvantage of switching diodes lies in a less efficient charge transfer rate and a higher capacitance, which can lead to cross talk.…”
Section: Introductionmentioning
confidence: 99%
“…Other possible applications may be found in the field of biotechnology, in particular in genomic analysis for the massively-parallel DNA detection. The single-switching diode readout technique is used to simplify device design and fabrication [3][4][5]. Recently, Fixe et al have reported on the use of an a-Si:H photodetector to measure the density of fluorescently-tagged biomolecules [2].…”
Section: Introductionmentioning
confidence: 99%